Pengaruh Pengetahuan Perpajakan, Relawan Pajak, dan Pertimbangan Pasar Kerja Terhadap Minat Berkarir di Bidang Perpajakan - Andes Wahyu Hidayah; Ita Rakhmawati (P3M Politeknik Negeri Bengkalis, 2025)
This research aims to examine the impact of tax knowledge, engagement in the Tax Volunteer program, and labor market considerations on students’ interest in pursuing careers in taxation. Employing a quantitative methodology, the study involved 116 students who took part in the Tax Volunteer program organized by the Regional Office I of the Directorate General of Taxes (DGT) in Central Java. Data were obtained through structured questionnaires and processed using multiple linear regression analysis with IBM SPSS Statistics 25. The results reveal that the three independent variables exert a positive and statistically significant influence on students’ career interest. These findings imply that experiential learning, particularly through participation in the Tax Volunteer program, plays a vital role in fostering interest in taxation-related professions. The coefficient of determination (R²) of 0.503 indicates that the model accounts for 50.3% of the variation in career interest. This underscores the importance of integrating theoretical instruction with practical exposure in cultivating students’ professional aspirations. Nevertheless, the study is limited by its narrow regional coverage, which may affect the generalizability of the results. It is therefore recommended that future research extend the geographical scope to provide broader insights into the determinants of career interest in taxation.